Pulmonary magnetic resonance-guided online adaptive radiotherapy of locally advanced non-small-cell lung cancer: the PUMA trial - Regnery, Sebastian; de Colle, Chiara; Eze, Chukwuka; Corradini, Stefanie; Thieke, Christian; Sedlaczek, Oliver; Schlemmer, Heinz-Peter; Dinkel, Julien; Seith, Ferdinand; Kopp-Schneider, Annette; Gillmann, Clarissa; Renkamp, Claudia Katharina; et al. (Radiation oncology, 2023)
Patients with locally-advanced non-small-cell lung cancer (LA-NSCLC) are often ineligible for surgery, so that definitive chemoradiotherapy (CRT) represents the treatment of choice. Nevertheless, long-term tumor control is often not achieved. Intensification of radiotherapy (RT) to improve locoregional tumor control is limited by the detrimental effect of higher radiation exposure of thoracic organs-at-risk (OAR). This narrow therapeutic ratio may be expanded by exploiting the advantages of magnetic resonance (MR) linear accelerators, mainly the online adaptation of the treatment plan to the current anatomy based on daily acquired MR images. However, MR-guidance is both labor-intensive and increases treatment times, which raises the question of its clinical feasibility to treat LA-NSCLC. Therefore, the PUMA trial was designed as a prospective, multicenter phase I trial to demonstrate the clinical feasibility of MR-guided online adaptive RT in LA-NSCLC.
Gesehen am 05.07.2023